Geographies of tourism knowledge: scientific networks and territorial inequalities in public universities of Andalusia, Spain (2010-2023) - Medeiros Robaina, Igor Martins; Montoya Pérez, Daniel; Fioravante, Karina (Geografares, 2025)
This study analyzes the institutionalization and scientific production of Tourism degree programs in public universities of Andalusia between 2010 and 2023, from the perspective of Geographies of Knowledge. To this end, a methodological design is adopted that combines institutional sources, bibliometric indicators, and academic network analysis. The results reveal that the location of universities conditions their capacity to attract students, faculty precariousness constrains the accumulation of scientific capital, and research output growth remains uneven across institutions. These findings confirm that tourism knowledge is mainly produced in specific territories and framed within power relations, where universities act as epistemic nodes embedded in global hierarchies. International collaborations, oriented towards Ibero-America and marginally towards Africa, reinforce the idea that knowledge circulates in selective geographic circuits, combining cultural affinity with asymmetries in academic access and production.